"The Future of the Front National in France" - ARNOLD, EDWARD JAMES (My University, 2009)
The Future of the Front National in France The movement is not a spent force which will disappear with the demise of J-M Le Pen despite poor electoral results since 2007. Sarkozy appears to have occupied the political space and rhetoric of the FN with themes of cross-class appeal, and has infused his presidency with Gaullist energy on the international scene, but the conditions that have led in the past to the political success of the National Front are still present within the fabric of French society and politics. The decline in support for the FN is a symptom of an apparent return of the electors to supporting government parties. In 2007, votes for far left movements were also historically low. The conditions that have led in the past to the political success of the National Front are still present within the fabric of French society and politics. The social and urban fracture will be exacerbated by the recession that is on the horizon, and much higher levels of unemployment which has fed frontist success the the past is inevitable (cf the article by Hugues Lagrange, Emeutes, renovation urbaine et alienation politique, Revue francaise de science politique, juin 2008). The radicalisation of French muslims and themes of insecurity exacerbate tensions that feeds support for the FN as do thecurrent poliical and economic crises. The tactical nature of voting in the last election gave Sarkozy his victory, and reflects a rejection of the political class that is being reinforced by the "Sarko show". This score was hardly what could be described as a landslide (53.06%, or 2,192,698 votes more) and can be partly interpreted as an attempt to punish establishment figures, and to sanction the parliamentary Left for its failure to win a third consecutive presidential election and to prevent the apparent implosion of the parliamentary and radical left. This was manifested by support for the centrist Bayrou. In the first round of the presidential 34 elections, Sarkozy failed to make inroads among the youngest voters and unskilled manual voters, the prime supporters of the FN up until recently (cf Perrineau). Some of his policies towards young people in the banlieues and his support for what is seen to be high-handed police tactics against these groups have been seen to exacerbate tensions within French society. His attacks on republican values and an ambiguous attitude on separation of church and state is seen as an apparent promotion of communautarisme. The study of opinion polls shows clearly that a sizeable proportion of those interviewed have very little confidence or trust in political parties or politicians, and consider many of them to be corrupt (cf Chirac, Dumas etc). This theme of corruption has consistently fed the political fortunes of Le Pen since the mid 1980s. These are issues among others that have fed dissatisfaction with what Le Pen has called "l'etablissement" and -given the right context of societal dislocation and crisis- accounts for the past success of the Front National as a political force. The troubled economic times that we are now living in can quickly erode the enthusiasm for new political modes such as Sarkozyism and reopen the way for extremist politics as embodied by the FN.
23rd Annual Conference Violence in French History (The Society for the Study of French History)
PRESENTED
Trinity College Dublin
Keywords: National Front, Le Pen; France